Reading of Al-Qur'an Verses In The "Dikia Rabano" Tradition - Ramadhanul Ikhsan; Cisia Padila; Dedek Saputra; Sasmi Nelwati; Ahmad Sabri (al-Afkar, Journal For Islamic Studies, 2025)
This research originated from the phenomenon of community religious traditions in the West Sumatra region, precisely in Jorong Halalang. The local community named it Dikia Rabano. In this tradition there is a series of Al-Qur'an verses that are read before starting the recitation of sholawat to the prophet. The formulation of the problem is how is the transformation of the recitation of the Qur'anic verses in the Dikia Rabano tradition? and how is the public perception of the Qur'anic verses in the Dikia Rabano tradition? This research is a field research (Field research) whose data collection techniques the author uses observation, interviews, and documentation. The primary data sources are traditional leaders, religious leaders, teachers and members of Dikia Rabano and the community in Jorong Halalang Nagari Kamang Mudiak. To analyze the data, the author uses data reduction steps, data analysis and finally conclusions. From the results of the study it can be concluded that the transformation of the recitation of the Qur'anic verses read in the Dikia Rabano tradition, that the practice of reading these verses has existed since the time of the Prophet which then continued in the generations after him. As for the public perception of the Qur'anic verses read in the Dikia Rabano tradition, including as protection to be given a smooth event, it is also understood as a means to ask for the blessing of reading shalawat to be conveyed to the Prophet Muhammad so as to get syafa'at from him in the afterlife, one form of khidmat to teachers and previous scholars by following their teachings, heart healers when read in tahlilan events and for expressions of gratitude when read in events related to thanksgiving and celebrations and as a form of worship to Allah SWT.